(untitled) (Annual of the Faculty of Philosophy in Skopje, 2024)
The difference in attitudes, interests and influences of the great powers contributed to greater uncertainty and fear for the future of nations and states. In the past decade, revisionist and autocratic countries such as Russia and China have sought to shift the focus from the West to the East and build a “post-Western world order” that will reshape the world against American values and interests. In this new period of transition, which resembles the time of the Cold War, the traditional security-military issues of the balance of power, the arms race, the struggle for territories and the strengthening of alliances are being emphasized again. A possible confrontation between the great powers, where the United States of America is still the leading power in the world, while the PRC is the second economic and military power, and Russia is one of the two most powerful nuclear powers, could threaten global and regional security and stability. The sharpened geopolitical rivalry between the “big three” will increase tensions in their spheres of interest, that is, in the regions and countries that are located on the strategic lines of separation. The focus of attention is on Eastern Europe and the Indo-Pacific region, which are of great geostrategic importance for the great powers and their alliances. Due to the historical connection with these “exclusive zones of interest”, there is a possibility that the previous “competitive coexistence” will escalate into an intense security rivalry.